1995
DOI: 10.1109/89.466662
|View full text |Cite
|
Sign up to set email alerts
|

Determination of instants of significant excitation in speech using group delay function

Abstract: A new method for determining the instants of significant excitation in speech signals is proposed. Here, significant excitation refers primarily to the instant of glottal closure within a pitch period in voiced speech. The method is based on the global phase characteristics of minimum phase signals. The average slope of the unwrapped phase of the short-time Fourier transform of linear prediction residual is calculated as a function of time. Instants where the phase slope function makes a positive zerocrossing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
120
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 176 publications
(121 citation statements)
references
References 8 publications
1
120
0
Order By: Relevance
“…From the clean speech the voiced/ unvoiced/silence segments and the instants of signi®cant excitation were identi®ed (Smits and Yegnanarayana, 1995;Yegnanarayana and Teunen, 1994). The LP residual signal of noisy speech was modi®ed retaining only the 2 ms portions of the residual signal around the instants of excitation.…”
Section: Nature Of Lp Residual Signalmentioning
confidence: 99%
“…From the clean speech the voiced/ unvoiced/silence segments and the instants of signi®cant excitation were identi®ed (Smits and Yegnanarayana, 1995;Yegnanarayana and Teunen, 1994). The LP residual signal of noisy speech was modi®ed retaining only the 2 ms portions of the residual signal around the instants of excitation.…”
Section: Nature Of Lp Residual Signalmentioning
confidence: 99%
“…The instants of significant excitation can be derived from the LP residual signal as follows: Around each sample a 10 ms segment of the LP residual signal is considered, and the group delay function τ (ω) is computed using [18] filter to remove any discontinuities in the group delay function. The negative of the average of the smoothed group delay function is called phase slope [17]. The phase slope value is computed at each sampling instant to obtain the phase slope function.…”
Section: Proposed Methods For Duration Modificationmentioning
confidence: 99%
“…The instants of significant excitation (GCIs) are computed from the LP residual using group delay analysis [17]. The instants of significant excitation can be derived from the LP residual signal as follows: Around each sample a 10 ms segment of the LP residual signal is considered, and the group delay function τ (ω) is computed using [18] filter to remove any discontinuities in the group delay function.…”
Section: Proposed Methods For Duration Modificationmentioning
confidence: 99%
“…The authors reported significant improvements in performance, computational complexity and noise robustness. The method proposed in [8] estimates the location of the excitation within an analysis frame as the average value of the group delay. Recently, work on energy flow in the lossless-tube model has been reported [10] and it was suggested that the signal representing acoustic input power at the glottis can be used to determine the instants of glottal closure and opening.…”
Section: Segmentation Of the Larynx Cyclementioning
confidence: 99%
“…In this paper, the APLAWD database [11] has been used to perform comparative evaluations of three methods for estimating GCIs in voiced speech using Wong's LPC residual (LPCR) [6], the Frobenius Norm (FN) [7] and the Group Delay (GD) [8]. APLAWD contains phonetically balanced speech from 5 male and 5 female talkers as well as EGG recordings from which, after time-alignment, reference GCIs have been extracted using the HQTx algorithm [9].…”
Section: Segmentation Of the Larynx Cyclementioning
confidence: 99%